2006
DOI: 10.1021/bi062148m
|View full text |Cite
|
Sign up to set email alerts
|

Micelle-Induced Folding of Spinach Thylakoid Soluble Phosphoprotein of 9 kDa and Its Functional Implications,

Abstract: Thylakoid soluble phosphoprotein of 9 kDa (TSP9) has been identified as a plant-specific protein in the photosynthetic thylakoid membrane (Carlberg et al., Proc. Natl. Acad. Sci. 2003, 100, 757-762). Non-phosphorylated TSP9 is associated with the membrane, whereas after light-induced phosphorylation, a fraction of the phosphorylated TSP9 is released into the aqueous stroma. By NMR spectroscopy, we have determined the structural features of non-phosphorylated TSP9 in both aqueous solution and in membrane mimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Micelles formed by SDS have been used to mimic membranes and have consistently been shown to induce secondary structure, whereas TFE is widely known to induce structure formation. 34,35 Taken together, the results indicate that the isolated DSCR, while intrinsically disordered in solution, is able to adopt regular structure at physiological temperatures and in the presence of alcohols and micelles and hint that a biological context could also stabilize its nascent structure.…”
Section: Secondary-structure Analysis Of Dscrmentioning
confidence: 79%
“…Micelles formed by SDS have been used to mimic membranes and have consistently been shown to induce secondary structure, whereas TFE is widely known to induce structure formation. 34,35 Taken together, the results indicate that the isolated DSCR, while intrinsically disordered in solution, is able to adopt regular structure at physiological temperatures and in the presence of alcohols and micelles and hint that a biological context could also stabilize its nascent structure.…”
Section: Secondary-structure Analysis Of Dscrmentioning
confidence: 79%
“…Several lines of data show that TSP9 is a highly disordered protein, lacking a unique structure under physiological conditions (19). Proteins with high intrinsic disorder form a newly recognized class of proteins (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Upon phosphorylation, TSP9 is partially released from the membrane, and we have suggested that it could play a role in chloroplast signaling (18). NMR spectroscopic studies have shown that TSP9 is highly disordered in aqueous solution but adopts a more ordered conformation under membrane mimetic conditions (19). Intrinsically disordered proteins form a growing family of proteins commonly involved in recognition, regulation, and cell signaling that has only recently been recognized, presumably due to a strong bias in classical biochemical methods toward folded proteins (for reviews, see Refs.…”
mentioning
confidence: 97%
“…Regions of IDP can exist as unfolded chains or molten globules with well-developed secondary structure and often function through transition between differently folded states (2). Mechanisms for functional conformational transition include binding with other proteins, nucleic acids, various small molecules and numerous posttranslational modifications, such as phosphorylation, which has been shown to be especially important (3,4). Biological functions of known IDPs are varied and their roles include the following: instigation of protein complex formation, molecular recognition as seen in nucleoporins of the nuclear pore complex (5), signal transduction, transcriptional regulation and many other functions (6,7) too numerous to list here.…”
Section: Introductionmentioning
confidence: 99%